Organoaxial volvulus of descending colon: a case report - Dhinadhayalan, Rajasree; T., Lokesh Kumar; Naik, Shailendra Singh; B., Padhmini (International Journal of Research in Medical Sciences, 2020)
“Colonic volvulus” refers to the twisting of colon, which most commonly involves sigmoid colon causing obstruction, ischemia and gangrene. But very rarely segment of descending colon can be involved. This is a case of 42 year old male with vomiting, abdomen pain and distension since one day, showing organoaxial volvulus of descending colon loop with a twist of mesentery.